1996
DOI: 10.1177/0013161x96032001002
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the Principal's Role in School Effectiveness: A Review of Empirical Research, 1980-1995

Abstract: Although the is little disagreement conquering the belief that principals have an impact on the lives of teachers and students, both the nature and degree of this effect continues to be open to debate. The relationship is complex and not easily subject to empirical verification. This article reviews the empirical literature on the relationship between the principal's role and school effectiveness during the period from 1980 to 1995. We specifically focus on the conceptual underpinnings of several theoretical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
949
4
65

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,086 publications
(1,055 citation statements)
references
References 37 publications
37
949
4
65
Order By: Relevance
“…There is an interesting tension here. In much of the professional leadership and school effectiveness literature, it is suggested that the principal as 'out-front leader' and 'driver' is a vital ingredient in establishing and maintaining positive, purposive change in an implementation programme (Hallinger & Heck, 1996;Southworth, 2002;Leithwood, Harris, & Hopkins, 2008). On the other hand, in other literature it is suggested that unless teachers also see themselves as fully involved and as genuine co-leaders in the whole professional learning community, meaningful change will not 'scale up' to include all teachers and classrooms (Eaker, DuFour, & DuFour, 2002;Bain, 2007).…”
Section: Principal As Leadermentioning
confidence: 99%
“…There is an interesting tension here. In much of the professional leadership and school effectiveness literature, it is suggested that the principal as 'out-front leader' and 'driver' is a vital ingredient in establishing and maintaining positive, purposive change in an implementation programme (Hallinger & Heck, 1996;Southworth, 2002;Leithwood, Harris, & Hopkins, 2008). On the other hand, in other literature it is suggested that unless teachers also see themselves as fully involved and as genuine co-leaders in the whole professional learning community, meaningful change will not 'scale up' to include all teachers and classrooms (Eaker, DuFour, & DuFour, 2002;Bain, 2007).…”
Section: Principal As Leadermentioning
confidence: 99%
“…Policy makers' emerging emphasis on improving teaching and learning led to an interest in the concept of principal instructional leadership in the USA (e.g., Leithwood and Montgomery, 1982;Hallinger and Murphy, 1986;Marcoulides and Heck, 1992;Hallinger and Heck, 1996), and England (e.g., Day et al, 2001;Southworth, 2002;MacBeath and Swaffield, 2008). However, there has been very little discussion in Greece about how leadership is conceptualized by school practitioners and whether leadership contributes to school improvement (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The hope for finding such an effective school leader model, however, has dampened with the findings of several meta-analyses (Hallinger & Heck, 1996;Witziers, Bosker, & Krüger, 2003). These studies revealed that the immediate effects of educational leadership on school performance were marginal.…”
Section: Introductionmentioning
confidence: 99%